Soft X-ray measurement by SPPD11-04 detectors on the PF “Tulip” installation - Eliseev, S.P.; Nikulin, V.Ya.; Silin, P.V. (Вопросы атомной науки и техники, 2008)
The soft X-ray (SXR) measurements were received with help of the fast semiconductor detectors SPPD11-04 with exposure time about 1.5 ns. Observation directions were at 45° and 90° to the chamber axis. The SXR dependence from pressure was designed. The radiation maximum corresponded to argon pressure equals to 2 Torr. The full width at half-maximum of the pulse at this pressure and a voltage of 12 kV was 5 ns. The SXR radiation dependence was investigated from the capacitor banks voltage (8-14 kV) in the two ranges of energy 1.2-1.8 and 2.9-3.5 keV. At the voltage of 14 kV and an argon pressure of 2 Torr the quantity of radiation quanta was estimated about 8·10¹⁴, the total radiation energy ~ 0.2 J and power ~ 7·10⁶ W in 4π geometry. За допомогою швидкодіючих напівпровідникових детекторів типу СППД11-04 проведені виміри м'якого рентгенівського випромінювання (МРВ) з часовим дозволом 1.5 нс. Здійснено спостереження під кутами 45 і 90˚ до вертикальної осі системи. Досліджено залежність інтенсивності МРВ від тиску газу. Максимум випромінювання відповідав тискові аргону 2 Торр. Ширина рентгенівського імпульсу по напіввисоті при даному тиску і напрузі 12 кВ дорівнювала 5 нс. Була досліджена залежність МРВ від напруги конденсаторної батареї (8-14 кВ) у двох енергетичних діапазонах квантів 1.2-1.8 і 2.9-3.5 кеВ. Для даних діапазонів при напрузі 14 кВ і тиску аргону 2 Торр оцінені повна кількість квантів 8·10¹⁴, повна енергія ~ 0.2 Дж і потужність випромінювання ~ 7·10⁶ Вт у 4π. С помощью быстродействующих полупроводниковых детекторов типа СППД11-04 проведены измерения мягкого рентгеновского излучения (МРИ) с временным разрешением 1.5 нс. Осуществлено наблюдение под углами 45 и 90˚ к вертикальной оси системы. Исследована зависимость интенсивности МРИ от давления газа. Максимум излучения соответствовал давлению аргона 2 Торр. Ширина рентгеновского импульса по полувысоте при данном давлении и напряжении 12 кВ равнялась 5 нс. Была исследована зависимость МРИ от напряжения конденсаторной батареи (8-14 кВ) в двух энергетических диапазонах квантов 1.2-1.8 и 2.9-3.5 кэВ. Для данных диапазонах при напряжении 14 кВ и давлении аргона 2 Торр оценены полное количество квантов 8·10¹⁴, полная энергия ~ 0.2 Дж и мощность излучения ~ 7·10⁶ Вт в 4π.